Preparation method of adsorbent for producing high-purity silane and adsorbent

By preparing an adsorbent with a CuO/AC core and a molecular sieve shell, the problem of insufficient silane purification capacity in existing technologies was solved, achieving efficient adsorption of B2H6 and PH3 in silanes, improving the purity of silanes, and meeting the application requirements of electronic-grade silanes.

CN121003974APending Publication Date: 2025-11-25SHAANXI SAINENG RUIKE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511150229.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively adsorb trace amounts of B2H6 and PH3 impurities in silanes, resulting in insufficient silane purity and affecting the performance of semiconductor and photovoltaic industries.

Method used

An adsorbent consisting of a CuO/AC core and a molecular sieve shell is formed by mixing oxidized activated carbon with a copper salt precursor, followed by calcination and hydrothermal reaction with sodium aluminosilicate sol and a template agent. This process utilizes the chemical activity of CuO and the confinement effect of the molecular sieve to achieve deep purification of impurities in silanes.

Benefits of technology

It increases the adsorption capacity of B2H6 and PH3 in silanes, meets the purity requirements of electronic-grade silanes, and improves the performance of semiconductor and photovoltaic industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of an adsorbent for producing high-purity silane and the adsorbent. The method comprises the following steps: step 1, carrying out oxidation treatment on activated carbon; 2, uniformly mixing the sample obtained in the step 1 with a copper salt precursor; 3, calcining the sample obtained in the step 2 in an inert atmosphere to obtain a CuO / AC inner core; step 4, dispersing the CuO / AC inner core into the sodium aluminosilicate sol, and then adding a template agent to carry out hydrothermal reaction, so that sodium aluminosilicate is crystallized to obtain an adsorbent precursor; and step 5, roasting the adsorbent precursor to obtain the adsorbent. The adsorbent is provided with a CuO / AC inner core and a molecular sieve shell, when impurities are adsorbed, the molecular sieve shell preliminarily adsorbs borane and phosphorane in silane, and deep purification is achieved through Cu ions in the CuO / AC inner core; meanwhile, the high conductivity of the activated carbon promotes electron transfer, and the reaction between Cu ions and phosphorane / borane is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of adsorption materials, and particularly relates to a preparation method of an adsorbent for producing high-purity silane and the adsorbent. BACKGROUND

[0002] Silane (SiH4) is an irreplaceable precursor for the semiconductor, photovoltaic and advanced display industries, and the purity of the silane must reach more than 6N (impurities < 1 ppb), otherwise trace amounts of boron and phosphorus elements will form deep level defects in the crystal lattice, resulting in threshold voltage drift, rapid decrease of minority carrier lifetime and surge of leakage current, ultimately causing a 10-30% decrease in chip yield and a 1-2% loss in photovoltaic module efficiency. At present, the global annual demand for silane has exceeded 150,000 tons, of which 90% needs to be deeply purified before being used for 12-inch wafers and TOPCon cells. Industrial silane is usually prepared from metallurgical-grade silicon through a chlorination-disproportionation-distillation combined process, and 10-100 ppm of impurities such as B2H6 and PH3 remain in the crude product. The adsorption of B2H6 by traditional 4A, 5A or 13X molecular sieves is mainly physical adsorption, and the adsorption capacity is weak, with limited adsorption capacity at room temperature; the adsorption capacity of traditional 5A molecular sieves for PH3 is only 6.68 mg / g at room temperature, and the adsorption capacity is weak.

[0003] Therefore, developing a new type of adsorbent that can simultaneously adsorb B2H6 and PH3 has become the key to breaking through the bottleneck of silane deep purification. SUMMARY

[0004] The first technical problem to be solved by the present application is to provide a preparation method of an adsorbent for producing high-purity silane in view of the status of the prior art.

[0005] The second technical problem to be solved by the present application is to provide an adsorbent prepared by the above preparation method in view of the status of the prior art.

[0006] The technical solution adopted by the present application to solve the first technical problem is as follows: a preparation method of an adsorbent for producing high-purity silane, comprising the following steps:

[0007] Step 1: oxidizing activated carbon;

[0008] Step 2: uniformly mixing the sample obtained in step 1 with a copper salt precursor;

[0009] Step 3: calcining the sample obtained in step 2 under an inert atmosphere to obtain a CuO / AC inner core;

[0010] Step 4: dispersing the CuO / AC inner core in a sodium aluminosilicate sol, and then adding a template agent to perform a hydrothermal reaction, so that the sodium aluminosilicate sol is crystallized, thereby obtaining an adsorbent precursor;

[0011] Step 5: calcining the adsorbent precursor to obtain an adsorbent.

[0012] Preferably, in step 1, the activated carbon is selected from at least one of coal-based activated carbon, coconut shell-based activated carbon and wood-based activated carbon; and the activated carbon is subjected to oxidation treatment with a nitric acid solution having a mass concentration of 10-20%. The activated carbon can provide a high specific surface area (>1000 m / g), thereby enhancing the dispersibility of CuO and simultaneously physically adsorbing impurity molecules.

[0013] Preferably, in step 1, the activated carbon is subjected to oxidation treatment with a nitric acid solution as follows: the activated carbon is treated with a nitric acid solution having a mass concentration of 15% at 120°C for 3h, so as to expand the pore volume of the activated carbon and introduce carboxyl / hydroxyl functional groups on the activated carbon; wherein the carboxyl / hydroxyl functional groups can enhance the Cu 2+ anchoring ability.

[0014] Preferably, in step 2, the copper salt precursor is selected from a copper nitrate solution having a concentration of 0.4-1M, and the sample obtained in step 1 is mixed with the copper nitrate solution under ultrasonic assistance. In other embodiments, the copper salt precursor can also be in the form of a copper nitrate solid.

[0015] Preferably, in step 2, the copper salt precursor is selected from a copper nitrate solution having a concentration of 0.5M.

[0016] Preferably, in step 3, the inert atmosphere is a nitrogen or argon atmosphere, the calcination temperature is 250-350°C, and the calcination time is 0.2-5h. Step 3 generates CuO nanoparticles with high dispersibility, and the copper oxide loading is 5-20% by mass. A copper oxide loading that is too low will result in insufficient catalytic activity, and a copper oxide loading that is too high will block the pore channels of the activated carbon and reduce the specific surface area; the CuO as an active component captures phosphine (PH3) and borane (B2H6) through complexation.

[0017] Preferably, the copper oxide loading is 12-15% by mass.

[0018] Preferably, in step 3, the inert atmosphere is a nitrogen atmosphere, the calcination temperature is 300°C, and the calcination time is 2h.

[0019] Preferably, in step 4, the molar ratio of SiO2 to Al2O3 in the sodium aluminosilicate is 2.0, and the viscosity of the sodium aluminosilicate sol is 20-50 mPa·s.

[0020] Preferably, the template agent is tetrapropylammonium hydroxide; and the molar ratio of the tetrapropylammonium hydroxide to the SiO2 is 0.1-0.2. When the molar ratio of the tetrapropylammonium hydroxide to the SiO2 is 0.1-0.2, the crystallinity of the molecular sieve and the dispersibility of the CuO can be well balanced.

[0021] Preferably, in step 4, the temperature of the hydrothermal reaction is 100-120℃; and the time of the hydrothermal reaction is 20-28h.

[0022] Preferably, in step 5, the temperature of the calcination is 500-600℃. During the calcination, the tetrapropylammonium hydroxide is decomposed and volatilized, so that a 50-100μm thick zeolite shell is formed on the periphery of the CuO / AC core; the zeolite shell can preliminarily physically adsorb the phosphine and borane in the silane, and at the same time, protect the core and avoid the impurities produced by the chemical adsorption of the core from entering the silane.

[0023] Preferably, in step 5, the adsorbent comprises the CuO / AC core and the 50-100μm thick zeolite shell wrapped outside the CuO / AC core.

[0024] Preferably, the specific surface area of the zeolite is 550-640m 2 / g, and the porosity of the zeolite is 40-52%.

[0025] Preferably, the micropore volume of the zeolite is 0.25-0.35cm 3 / g, and the pore size of the zeolite is 0.45-0.55nm.

[0026] The present application solves the second technical problem by using the adsorbent prepared by the above method.

[0027] Compared with the prior art, the present application has the following advantages: the adsorbent prepared by the present application has a CuO / AC core and a zeolite shell; when adsorbing impurities, the zeolite shell preliminarily adsorbs the borane and phosphine in the silane, and then the Cu ions in the CuO / AC core realize deep purification through the chemical activity; at the same time, the high conductivity of the activated carbon promotes the transfer of electrons, accelerates the reaction of the Cu ions and the phosphine / borane, and the "confinement effect" of the zeolite can limit the phosphine / borane gas in the CuO / AC core, thus improving the reaction efficiency. DETAILED DESCRIPTION

[0028] The present application will be further described in detail below with reference to the examples.

[0029] Example 1

[0030] Step 1: 30-mesh activated carbon (AC) was immersed in a 15vol% nitric acid solution for 3h, then treated with ultrasonic oscillation for 0.5h, and finally washed with ultrapure water for 5-6 times. Subsequently, it was transferred to a blast drying oven and dried at 100℃ for 12h to obtain an activated carbon carrier; the specific surface area of the activated carbon carrier was 1017m 2 / g, the pore volume was 0.42cm 3 / g, and the average pore size was 2nm.

[0031] Step 2: 2 g of the above activated carbon support was put into 20 mL of 0.5 M copper nitrate solution while mixing the two by ultrasonic assistance;

[0032] Step 3: The sample obtained in Step 2 was calcined at 300 °C for 2 h using a tube furnace under nitrogen atmosphere protection to obtain CuO / AC core, which was highly dispersed nanoparticles with a copper oxide loading of 12-15%;

[0033] Step 4: 2 g of CuO / AC core was dispersed in 20 mL of sodium aluminosilicate sol with a viscosity of 35 mPa-s, in which the molar ratio of SiO2 to Al2O3 of the sodium aluminosilicate was 2.0, and tetrapropylammonium hydroxide was added, with a molar ratio of tetrapropylammonium hydroxide to SiO2 of 0.15, followed by hydrothermal reaction at 110 °C for 24 h to crystallize the sodium aluminosilicate sol. The solid obtained by hydrothermal reaction was taken out and washed with ultrapure water three times, and dried at 100 °C in a blast drying oven for 12 h to obtain an adsorbent precursor;

[0034] Step 5: The adsorbent precursor was calcined at 550 °C to obtain an adsorbent with a stable pore structure. The adsorbent comprises a CuO / AC core and a 75 μm molecular sieve shell wrapped outside the CuO / AC core, wherein the specific surface area of the molecular sieve is 550 m 2 / g, the porosity of the molecular sieve is 48%, the micropore volume of the molecular sieve is 0.25 cm 3 / g, and the pore size of the molecular sieve is 0.55 nm. Dynamic breakthrough experiments were performed on the above adsorbent: SiH4 gas containing PH3 / B2H6 (1-10 ppm) was introduced into a fixed bed reactor, and the outlet concentration was detected by GC-MS until the breakthrough point (outlet concentration > 1 ppb), and the adsorption capacity of the adsorbent was measured. The results are shown in Table 1.

[0035] Example 2

[0036] Step 1: 20 mesh activated carbon was immersed in a 10 vol% nitric acid solution for 4 h, then treated with ultrasonic oscillation for 0.5 h, and finally washed with ultrapure water for 5-6 times. Then it was transferred to a blast drying oven for drying at 100 °C for 12 h to obtain an activated carbon support;

[0037] Step 2: 2 g of the above activated carbon support was put into 20 mL of 0.4 M copper nitrate solution while mixing the two by ultrasonic assistance;

[0038] Step 3: The sample obtained in Step 2 was calcined at 350 °C for 0.2 h using a tube furnace under nitrogen atmosphere protection to obtain CuO / AC core, which was highly dispersed nanoparticles with a copper oxide loading of 12-15%;

[0039] Step 4: Disperse 2g of CuO / AC core in 20ml of sodium aluminosilicate sol with a viscosity of 20mPa·s, wherein the molar ratio of SiO2 to Al2O3 in sodium aluminosilicate is 2.0. Then add tetrapropylammonium hydroxide, wherein the molar ratio of tetrapropylammonium hydroxide to SiO2 is 0.15. Then, perform a hydrothermal reaction at 100℃ for 28h to crystallize the sodium aluminosilicate sol. Take out the solid obtained from the hydrothermal reaction and wash it three times with ultrapure water. Dry it in a forced-air drying oven at 100℃ for 12h to obtain the adsorbent precursor.

[0040] Step 5: The adsorbent precursor is calcined at 550℃ to obtain an adsorbent with a stable pore structure. The adsorbent consists of a CuO / AC core and a 100μm molecular sieve shell surrounding the CuO / AC core, wherein the molecular sieve has a specific surface area of ​​600m². 2 / g, the porosity of the molecular sieve is 40%, and the micropore volume of the molecular sieve is 0.30cm³. 3 / g, the molecular sieve has a pore size of 0.50nm. Dynamic breakthrough experiments were conducted on the above adsorbent: SiH4 gas containing PH3 / B2H6 (1~10ppm) was introduced into a fixed-bed reactor, and the outlet concentration was detected by GC-MS until the breakthrough point (outlet concentration >1ppb). The adsorption capacity of the adsorbent was measured and the results are shown in Table 1.

[0041] Example 3

[0042] Step 1: Impregnate 40-mesh activated carbon with a 20 vol% nitric acid solution for 3 hours, then treat with ultrasonic vibration for 0.5 hours, and finally wash with ultrapure water 5-6 times. Then transfer to a forced-air drying oven and dry at 100℃ for 12 hours to obtain the activated carbon carrier;

[0043] Step 2: Place 2g of the above activated carbon carrier into 20mL of 1M copper nitrate solution, and mix the two simultaneously with ultrasonic assistance;

[0044] Step 3: Under nitrogen atmosphere protection, the sample obtained in step 2 was calcined at 250℃ for 5h in a tube furnace to obtain CuO / AC core. The CuO / AC core is a highly dispersed nanoparticle with a copper oxide loading of 12-15%.

[0045] Step 4: Disperse 2g of CuO / AC core in 20ml of sodium aluminosilicate sol with a viscosity of 50mPa·s, wherein the molar ratio of SiO2 to Al2O3 in sodium aluminosilicate is 2.0. Then add tetrapropylammonium hydroxide, wherein the molar ratio of tetrapropylammonium hydroxide to SiO2 is 0.2. Then, perform a hydrothermal reaction at 120℃ for 20h to crystallize the sodium aluminosilicate sol. Take out the solid obtained from the hydrothermal reaction and wash it three times with ultrapure water. Dry it in a forced-air drying oven at 100℃ for 12h to obtain the adsorbent precursor.

[0046] Step 5: The adsorbent precursor is calcined at 600℃ to obtain an adsorbent with a stable pore structure. The adsorbent consists of a CuO / AC core and a 50μm molecular sieve shell surrounding the CuO / AC core, wherein the specific surface area of ​​the molecular sieve is 640m². 2 / g, the porosity of the molecular sieve is 52%, and the micropore volume of the molecular sieve is 0.35cm³. 3 / g, the molecular sieve has a pore size of 0.45nm.

[0047] Dynamic breakthrough experiments were conducted on the above adsorbents: SiH4 gas containing PH3 / B2H6 (1-10 ppm) was introduced into a fixed-bed reactor, and the outlet concentration was detected by GC-MS until the breakthrough point (outlet concentration > 1 ppb). The adsorption capacity of the adsorbent was measured and the results are shown in Table 1.

[0048] Table 1. Experimental Results of Adsorbent Performance

[0049]

[0050] This invention utilizes the high specific surface area of ​​AC (typically 500-1500 m²). 2 The presence of abundant surface functional groups (such as carboxyl and hydroxyl groups) enhances the physical adsorption of small molecule gases and provides a dispersion support for CuO, preventing its aggregation and indirectly improving adsorption efficiency. Simultaneously, loading nano-sized CuO via impregnation increases the number of adsorption active sites, thereby enhancing adsorption capacity. The adsorbent prepared in this invention is a core-shell composite material (CuO / AC (core) / 5A molecular sieve (shell)), which exhibits high adsorption capacity for boranes and phosphines in silanes, making it suitable for the purification of electronic-grade silanes.

Claims

1. A method for preparing an adsorbent for producing high-purity silanes, characterized in that, Includes the following steps: Step 1: Oxidize the activated carbon; Step 2: Mix the sample obtained in Step 1 with the copper salt precursor until homogeneous; Step 3: Calcine the sample obtained in Step 2 under an inert atmosphere to obtain the CuO / AC core; Step 4: Disperse the CuO / AC core in sodium aluminosilicate sol, then add a template agent to carry out a hydrothermal reaction, causing the sodium aluminosilicate to crystallize, thereby obtaining the adsorbent precursor; Step 5: Calcining the adsorbent precursor to obtain the adsorbent.

2. The preparation method according to claim 1, characterized in that: In step 1, the activated carbon is selected from at least one of coal-based activated carbon, coconut shell-based activated carbon, and wood-based activated carbon; the activated carbon is oxidized using a nitric acid solution with a mass concentration of 10-20%.

3. The preparation method according to claim 1, characterized in that: In step 2, the copper salt precursor is selected from 0.4-1M copper nitrate solution, and the sample obtained in step 1 is mixed with the copper nitrate solution using ultrasound assistance.

4. The preparation method according to claim 1, characterized in that: In step 3, the inert atmosphere is nitrogen or argon, the calcination temperature is 250–350℃, and the calcination time is 0.2–5h.

5. The preparation method according to claim 1, characterized in that: In step 4, the molar ratio of SiO2 to Al2O3 in sodium aluminosilicate is 2.0, and the viscosity of the sodium aluminosilicate sol is 20–50 mPa·s.

6. The preparation method according to claim 5, characterized in that: The template agent is tetrapropylammonium hydroxide; and the molar ratio of the tetrapropylammonium hydroxide to the SiO2 is 0.1 to 0.

2.

7. The preparation method according to claim 1, characterized in that: In step 4, the temperature of the hydrothermal reaction is 100–120°C; the time of the hydrothermal reaction is 20–28 h.

8. The preparation method according to claim 1, characterized in that: In step 5, the roasting temperature is 500–600℃.

9. The preparation method according to claim 1, characterized in that: In step 5, the adsorbent comprises a CuO / AC core and a 50-100 μm molecular sieve shell surrounding the CuO / AC core.

10. An adsorbent prepared by the preparation method according to any one of claims 1 to 9.